What explains the gender gap in top incomes in developing countries? - Oliva, Nicolás,Jara, H. Xavier,Rattenhuber, Pia (United Nations University World Institute for Development Economics Research, 2021)
Based on tax records data from Ecuador, we analyse gender differences in top income groups from 2008 to 2017. Ecuador represents an interesting case as it shares many trends with other countries in the region in terms of women's status in the labour market. While we observe a significant increase in the share of women at the top of the income distribution during this period, women remain underrepresented in top income groups, at 38.7 per cent in the top 10 per cent income group and 22.8 per cent in the top 0.1 per cent income group. The composition of total income-labour, business, and capital income-is broadly similar for men and women at the top, with the importance of business and capital increasing at the very top. However, while women's capital income is more concentrated on rental income from real estate, men are more likely to earn capital income from dividends and financial returns, and to figure as majority shareholders. In terms of observable characteristics, having (private) tertiary education is more important for women than men. In contrast, the effect of having a spouse who belongs to a top income group is more important for men than women. Finally, we observe a high degree of persistence in top incomes across gender, with around 80 per cent of individuals in the top 10 per cent group remaining in this group from year to year.
10.35188/UNU-WIDER/2021/049-8
Keywords: Graue Literatur; top incomes; gender inequality; tax records; capital incomes; Ecuador